Направление сил, действующих на листовой ферромагнетик, в зависимости от временных характеристик при МИОМ - Батыгин, Ю.В.; Гнатов, А.В.; Щиголева, С.А. (Електротехніка і електромеханіка, 2011)
In the article, the physical mechanism of pulse magnetic fields force action on thin-wall sheet ferromagnetic conducting plates is theoretically formulated and justified. It is shown that attracting forces caused by magnetic properties of the work object metal prevail at low working frequencies. Increasing frequencies over a specified threshold value results in attraction changing into repulsion caused by prevailing action of Lorenz forces resulted from electrodynamic interaction of external fields with induced eddy currents.